A Rare Case: Vesicholithiasis with Dermoid Cyst of Bladder - Nugroho, Laksono; Kholiq, Syahdat Nur (Brawijaya Journal of Urology, 2025)
Introduction. Ovarian dermoid cyst, also known as mature cystic teratoma (MCT), is the most common ovarian germ cell tumor in young women. Teratomas have been reported to occur in various sites and organs. Bladder teratoma is a very rare extragonadal tumor, moreover in adults. Although teratomas are known as benign lesions in childhood, they may act as malignant tumors when detected during adulthood. Case. A 64-year-old woman presented with left side low back pain and dysuria over a 6-month period. Kidney, ureter, and bladder (KUB) X-ray showed a large stone in the bladder with calcification on the left side of the abdomen. An ultrasonography revealed 4.1 cm x 3.1 cm ill-defined echogenic mass in the urinary bladder lumen. Cystoscopy revealed hair on the back of the stone. The diagnosis was made on cystoscopy and confirmed histopathologically. Complete excision was possible. The histopathology report showed a benign mature teratoma with ectodermal, mesodermal, and endodermal elements. The histopathological findings confirmed skin, adnexal structures (sweat glands, hair follicles), adipose, and fibroblastic tissue, which were consistent with those of a dermoid cyst. Conclusion. A bladder teratoma mimics the presentation of a bladder stone, clinically and radiologically. A dermoid cyst should be considered as a differential diagnosis, especially when the stone appears to be confined to the bladder wall during examination. Keywords: bladder, dermoid cys, vesicolithiasis